Molecular Variability Among Fusarium Oxysporum Isolates Infecting Plants in Different Agricultural Environments in Libya (Derna Academy Journal for Applied Sciences, 2024)
Fusarium oxysporum represents one of the most significant soilborne fungal pathogens affecting agricultural crops worldwide, causing devastating vascular wilt diseases that result in substantial economic losses. This comprehensive study investigates the molecular variability among F. oxysporum isolates collected from various agricultural environments across Libya, focusing on their genetic diversity, pathogenic potential, and adaptation mechanisms. The research employs advanced molecular techniques including PCR-ITS analysis, DNA sequencing, and phylogenetic studies to characterize the population structure and evolutionary relationships of these isolates. Libya's diverse agricultural zones, ranging from Mediterranean coastal regions to desert oasis systems, provide unique ecological niches that may influence fungal genetic diversity and host specialization. Understanding the molecular variability of F. oxysporum in these environments is crucial for developing effective disease management strategies and resistant crop varieties. This study contributes to the global understanding of Fusarium diversity while addressing specific challenges faced by Libyan agriculture in the context of climate change and intensifying agricultural practices